Molecular Characterization of Haemoglobin E - Ejaz, Sara; Ghulam Mustafa; khaliq, Shagufta; Mohsin, Shahida (Journal of the Pakistan Medical Association, 2023)
Objectives: To detect mutation in cases having haemoglobin A2 level 7percent on high performance liquid chromatography. Method: The cross-sectional, descriptive study was conducted from July 2017 to December 2018 at the Department of Haematology and Human Genetics and Molecular Biology, University of Health Sciences, Lahore, Pakistan, and comprised patients of either gender with haemoglobin A2 7percent. The samples were collected from different cities of Punjab in collaboration with the Punjab Thalassemia Prevention Programme, Lahore. The samples were subjected to complete blood count and high performance liquid chromatography using automated haematology analysers and a beta thalassemia short programme, respectively. To analyse haemoglobin E mutations at the molecular level, polymerase chain reaction-restriction fragment length polymorphism (PCR_RFLP) was performed using a type IIS restriction endonuclease known as Mnl1 (derived from Moraxella nonliquefaciens) to cleave DNA at specific sites and the results were further confirmed on randomly selected samples using Sanger sequencing. Data was analysed using SPSS 25. Results: Of the 39 patients, 15(38.5percent) were males and 24(61.5percent) were females. The overall median age was 14 (23) years. There were 29 (74.4percent) patients a thalassemia family history, and 22(56.4percent) had a positive family history of transfusion related to thalassemia, while no patient had a family history of iron therapy. The media haemoglobin A, haemoglobin A2 and haemoglobin F levels were 72.2 (65.2-79.1) percent, 26.6 (19.1-34.0) percent and 0.9 (-0.8-2.6) percent, respectively. After molecular investigation, HbAE mutation was found in 23(59percent) patients, while wild type HbAA genotype was found in 16(41percent). The heterozygous HbE mutation was present in 23(59percent) patients. Conclusions: Frequently missed/undiagnosed cases of haemoglobin E that co-elute with haemoglobin A2 in the same high performance liquid chromatography window were detected among those with haemoglobin A2 7percent. Key Words: Haemoglobin E, Beta-thalassemia, High performance liquid chromatography, Restriction fragment length polymorphism.